Effects of preservative concentrations on larval cephalopharyngeal skeleton of Chrysomya megacephala (Fabricius, 1794) (Diptera: Calliphoridae), an alternative indicator to larval body length for mPMI estimation / Raja M. Zuha - Zuha, Raja M. (Faculty of Medicine, 2021)
Introduction: In forensic entomology, dipterous larval specimens found feeding on decomposing corpses are usually preserved in a range of 70-95% ethanol before being subjected to minimum postmortem interval (mPMI) assessment. However, larval body size, which is commonly used to infer mPMI, can be affected by preservatives resulting miscalculation of estimation. This study compared the effect of ethanol concentrations on larval body and cephalopharyngeal skeleton, a potential substitute to estimate larval age for mPMI estimation. Methods: Experiments were conducted on homogenised colony of Chrysomya megacephala (Fabricius, 1794) (Diptera: Calliphoridae) third instar larvae reared in similar conditions. They were fixed with hot water (80ºC) and preserved in 70% and 90% ethanol. After seven days in preservatives, larvae were measured for total body length from furthest part of the head to the last abdominal segment. Cephalopharyngeal skeleton was subsequently extracted from the body and measured based on morphometric landmarks on the pharyngeal sclerite. Centroid size of the cephalopharyngeal skeleton was also calculated based on the configuration of five morphometric landmarks. Results: In all four study replicates, pairwise comparisons with the original size indicated that larval body length was significantly affected by ethanol concentration (p<0.001) whilst only two of the study replicates showed cephalopharyngeal skeleton maintained its size when preserved in different ethanol concentration. Conclusion: Possible causes of variations are discussed herein with the results clearly indicated cephalopharyngeal skeleton should be considered as alternative growth parameter for mPMI estimation.